2009
DOI: 10.1016/j.physd.2009.02.012
|View full text |Cite
|
Sign up to set email alerts
|

A moving boundary problem motivated by electric breakdown, I: Spectrum of linear perturbations

Abstract: a b s t r a c tAn interfacial approximation of the streamer stage in the evolution of sparks and lightning can be written as a Laplacian growth model regularized by a 'kinetic undercooling' boundary condition. We study the linear stability of uniformly translating circles that solve the problem in two dimensions. In a space of smooth perturbations of the circular shape, the stability operator is found to have a pure point spectrum.Except for the eigenvalue λ 0 = 0 for infinitesimal translations, all eigenvalue… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
22
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 46 publications
2
22
0
Order By: Relevance
“…There are also linear stability results [7,34] and exact travelling waves for sufficiently large kinetic undercooling [7]. Closely related to the finger is the problem of a travelling finite bubble in a directed flow field, which is of recent interest in the literature on streamers [28,36,58]. Numerical solutions of the evolving shape of a bubble suggest that an initially smooth bubble boundary may not remain so for all time [36]; this property also arises in the present work.…”
Section: Introductionmentioning
confidence: 54%
“…There are also linear stability results [7,34] and exact travelling waves for sufficiently large kinetic undercooling [7]. Closely related to the finger is the problem of a travelling finite bubble in a directed flow field, which is of recent interest in the literature on streamers [28,36,58]. Numerical solutions of the evolving shape of a bubble suggest that an initially smooth bubble boundary may not remain so for all time [36]; this property also arises in the present work.…”
Section: Introductionmentioning
confidence: 54%
“…Propagating fronts in Laplacian growth occur naturally in quite a number of physical problems including viscous fingering [1,2,3,4,5], electro-chemical growth, dendritic crystal growth for small undercooling [6,7,8], and void migration in a conductor [9,10,11]. More recently, it has been shown that this class of problems includes the 'streamer' stage of electric breakdown [12,13,14,15,16,17,18,19], which will be described below. A central issue in these problems is the stability of curved fronts.…”
Section: Introductionmentioning
confidence: 99%
“…In two dimensions, a simple solution to the free boundary problem posed by this model takes the form of a uniformly translating circle. Our previous work in [17,18,19] and the present paper are primarily concerned with the linear and nonlinear stability of this solution to small perturbations. It is to be noted that the circular shape differs from an actual streamer shape.…”
Section: Introductionmentioning
confidence: 99%
“…Model reduction and analytical theory explained branching as a Laplacian instability that develops when the space charge layer around the streamer head is much thinner than the streamer radius [14]. Nevertheless, the analysis of a reduced movingboundary streamer model suggests that streamer heads are linearly stable [15,16] even if the stabilizing effects of electron diffusion and photo-ionization are neglected. Streamer fingers are therefore similar to laminar pipe flow: a finite perturbation is required to let streamers branch or to make the pipe flow turbulent.…”
mentioning
confidence: 99%